Pengaruh Video Interaktif Berbasis Masalah Terhadap Kemandirian Belajar Peserta Didik - Nuhaya, Nailan; Asyhari, Andi (JEID: Journal of Educational Integration and Development, 2023)
This study aims to determine the application of problem-based interactive videos to students' learning independence, learning independence before using problem-based interactive video media and the effect of problem-based interactive videos on students' learning independence on the concept of the human reproductive system. This type of research is experimental research with a quasi-experimental method of nonequivalent control group design. The results of the study stated that the application of problem-based interactive videos obtained student responses in the sufficient category. Independent learning of students before learning in the control class in the high category and the experimental class in the high category. There is an effect of problem-based interactive video that is oriented towards learning independence of students as evidenced by a test using the Mann-Whitney formula with the result of Sig (2-tailed) of 0.000 with a probability of 0.05 proving that sig (2-tailed) is smaller than the probability value.